Stanje populacije močvirskega krešiča Carabus variolosus (Coleoptera: Carabidae) v Natura 2000 območju Ličenca pri Poljčanah, SV Slovenija - Bedjanič, Matjaž (Acta entomologica slovenica (Ljubljana), 2021)
The distribution, relative abundances and conservation status of Carabus variolosus nodulosus Creutzer, 1799 was systematically surveyed for the first time in the Natura 2000 site Ličenca pri Poljčanah. In 2019 and 2020, the species was recorded at a total of 37 of the 52 sampled localities. It inhabits smaller forest streams, headwaters and marshy springs in the forested, hilly part of the area, while it doesn’t occur in the non-forested, flat parts of the area. Data on relative abundances at individual localities are presented. A narrow central conservation zone right next to forest streams and headwaters, where all forest management and other interventions must be strictly avoided is proposed.According to our assessment, the population of Carabus variolosus in the Natura 2000 site Ličenca pri Poljčanah is currently in a favorable conservation status.
Keywords: carabidae; Carabus variolosus; coleoptera; conservation status; distribution; Habitatna direktiva; Habitats directive; hygrophilous carabid; Natura 2000; razširjenost; Slovenia; Slovenija; varstveni status; vlagoljubni krešič; Žuželke